An optimal allocation model based on the regional ecological water requirements and multi-water supply characteristics: A case study of Shandong Province, China - Shanghong Zhang; Xiaoxiong Wen; Rongqi Zhang; Wei Miao; Zhiguo Gan (Journal of Hydrology: Regional Studies, 2023)
Study region: Shandong Province in China. Study focus: Multi-water supply can alleviate regional water scarcity. However, the regional water usage weakens ecological water requirements owing to cost management. And the simplified optimal allocation model usually considers regional external water purchase cost or departmental water consumption cost individually, while neglecting differences of multi-water sources in water quality, quantity, and overall costs, resulting in unreasonable utilization. The present work calculated both rigid and flexible water requirements based on different ecological objectives. Meanwhile, the improved model considering water quantity, cost, and quality was constructed, and in comparison to simplified model and actual allocation scheme. New hydrological insights for the region: Taking Shandong Province in 2020 as a case study, the rigid and flexible ecological water requirements are 1.35 and 1.74 times higher than the actual usage, respectively, reflecting the insufficient actual ecological water use. Compared to the simplified models that do not distinguish water source, the improved model can not only consider departmental water consumption costs, but also regional external water purchase costs, and result in a more reasonable water allocation. Compared to the actual water usage scheme, the present scheme reduces the water usage of the Yellow River and increases the water usage of Eastern Route, resulting in a more reasonable water allocation overall improved efficiency.